2013
DOI: 10.1371/journal.pone.0075299
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Light-Induced Yellow Leaf 1 Gene, Which Encodes a Geranylgeranyl Reductase, Affects Chlorophyll Biosynthesis and Light Sensitivity in Rice

Abstract: Chlorophylls (Chls) are crucial for capturing light energy for photosynthesis. Although several genes responsible for Chl biosynthesis were characterized in rice (Oryza sativa), the genetic properties of the hydrogenating enzyme involved in the final step of Chl synthesis remain unknown. In this study, we characterized a rice light-induced yellow leaf 1-1 (lyl1-1) mutant that is hypersensitive to high-light and defective in the Chl synthesis. Light-shading experiment suggested that the yellowing of lyl1-1 is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 59 publications
2
54
0
Order By: Relevance
“…The result showed that the majority of Chl molecules in the mutant were conjugated with an unsaturated geranylgeraniol side chain, in addition to small amount of normal Chl Phy (Figure 5;Tanaka et al 2010;Zhou et al 2013), indicated that the mutant has a defective OsCHL P. Therefore, we concluded the candidate gene underlying the 502ys mutant phenotype is OsChl P .
Figure 5 HPLC analysis of Chls. The elution profiles of wild type (a) , 502ys mutant (b) and 502ys/OsCHL P transgenic line (c) were detected at 660 nm.
…”
Section: Resultsmentioning
confidence: 88%
“…The result showed that the majority of Chl molecules in the mutant were conjugated with an unsaturated geranylgeraniol side chain, in addition to small amount of normal Chl Phy (Figure 5;Tanaka et al 2010;Zhou et al 2013), indicated that the mutant has a defective OsCHL P. Therefore, we concluded the candidate gene underlying the 502ys mutant phenotype is OsChl P .
Figure 5 HPLC analysis of Chls. The elution profiles of wild type (a) , 502ys mutant (b) and 502ys/OsCHL P transgenic line (c) were detected at 660 nm.
…”
Section: Resultsmentioning
confidence: 88%
“…Downregulation of GGR transcripts in transgenic tobacco using antisense RNA resulted in plants with less Chl and accumulating geranylgeranylated Chl, an intermediate compound suggesting GGR is required to increase Chl levels in plants (Tanaka et al, 1999). The rice yellow green leaf mutant, which has a single base mutation in the rice GGR (OsCHl P), exhibited reduced Chl levels and arrested chloroplast development (Zhou et al, 2013;Wang et al, 2014). By contrast, the significant decrease in pigment concentration observed in some of the lines showing high expression of the AdMYB7 transgene was intriguing.…”
Section: New Phytologistmentioning
confidence: 99%
“…S9). Of the analyzed potential partners, only OsGGR (Os02g51080), an enzyme that reduces GGPP into phytyl diphosphate for chlorophyll biosynthesis in thylakoid membranes (16,17), interacted with OsGGPPS1 ( Fig. 4A and SI Appendix, Fig.…”
Section: Osggpps1/osgrp Heterodimer Exists In a Multiprotein Complexmentioning
confidence: 99%